Anti-inflammatory Strategies in Atherosclerosis - Bugger, Heiko; Zirlik, Andreas (Hämostaseologie, 2021)
Atherosclerotic vascular disease and its related complications are the major cause of mortality in Western societies. Atherosclerosis is a chronic inflammatory disease of the arterial wall triggered by traditional and nontraditional risk factors and mediated by inflammatory and immune responses. Recent clinical trials provided compelling evidence corroborating that atherosclerosis is an inflammatory disease and demonstrated efficacy of anti-inflammatory interventions in reducing cardiovascular events and mortality. Traditional risk factors drive vascular inflammation, further justifying the instrumental role of intensified risk factor management in attenuating and preventing atherosclerotic disease and complications. Promising therapeutic approaches specifically related to inhibition of inflammation span traditional anti-inflammatory drugs, specific immunomodulation, and development of vaccination against atherosclerotic disease. Here, we review the inflammatory component in atherogenesis, the available evidence from clinical trials evaluating efficacy of therapeutic anti-inflammatory interventions in patients with high cardiovascular risk, and discuss potential future targets for anti-inflammatory or immune modulatory treatment in atherosclerotic cardiovascular disease.
Keywords: inflammation; atherosclerosis; strategies